Assessment of nanofiltration efficiency for simultaneous concentration of copper and recovery of acid from highly acidic wastewater - Bencheng Hu; Haowen Wu; Wenhao Su; Keyu Yao; Li Long; Pengfei Sun; Yongcheng Wang; Lin Lin; Hao Guo; Xiao-yan Li (Water Research, 2026)

Cross-species validation of conserved miR-504/PDHA1 and miR-500/EGLN2 interactions in sheep oocyte development - Junzheng Zhang; Jie Wang; Hao Li; Keyu Fu; Xu Han; Shuang Ji; Yi Jin (Theriogenology, 2026)

Quantifying lamina-controlled variations in rock physical properties from AI-reconstructed 3D multimineral digital rocks - Yuqi Wu; Yumei Ao; Jiabao Yang; Zijie Lu; Keyu Liu; Yuchen Fan; Jianhua Zhao; Li Hou; Bo Liao; Pejman Tahmasebi (International Journal of Rock Mechanics and Mining Sciences, 2026)

UAV-based measurements of methane emissions from two electrically-driven natural gas compressor stations in China - Tianran Han; Wang Tian; Yuheng Zhang; Jietao Zhou; Yanrong Yang; Keyu Chen; Lei Ren; Chuanfeng Wang; Yufei Huang; Haijiong Sun; Xinyi Chen; Chang Liu; et al. (Environmental Pollution, 2026)

Substitution of solid fats in model baked foods using emulsion-templated oleogels: Effects on microstructure, texture, and flavor - Junqing Han; Wenbo Miao; Qianzhu Lin; David Julian McClements; Keyu Lu; Zhengyu Jin; Zhitao Li; Chao Qiu (Food Bioscience, 2026)

Bacteria-inspired mechano-chemical nanovaccines enable multi-activation of dendritic cells for potent antitumor immunity - Hongjuan Zhao; Chenxi Zhao; Yuting Cang; Jinpei Sun; Qing Li; Keyu Zong; Yajing Wang; Di Meng; Qingling Song; Lei Wang (Chemical Engineering Journal, 2026)

Cu-doped BiOIO3 coupled with Co/Zn-ZIF for enhanced visible-light photocatalytic degradation of oxytetracycline: Synergistic effect and mechanistic insights - Maojie Zhang; Xinglin Li; Pengfei Zhu; Keyu Pu; Hongjie Xie (Journal of Environmental Chemical Engineering, 2026)

Modification of Lycium ruthenicum pomace dietary fibers: Enhanced physicochemical, structural, and functional properties - Huiling Li; Keyu Tian; Ruiqi Wang; Ruyu Shangguan; Jingna Yang; Nana Yang; Xintao Meng; Xiang Li; Ting Zhang; Hongjie Lei (Food Chemistry, 2026)

Circadian-based individualised protection against inflammation–cancer transition in atrophic gastritis patients - Ceng Shan; Min Guo; Feifan Feng; Xihong Wang; Mohang Li; Weichao Xu; Keyu Jia; Yifei Liu; Yifan Jia (EPMA Journal, 2026)

Numerical study on the dynamic characteristics of high-pressure hydrogen-oxygen premixed flame in combustion light gas gun - Junjie Lu; Qiuyang Zhao; Keyu Zhao; Tengyu Li; Yechun Wang; Hui Jin; Liejin Guo (Fuel, 2026)

From built-in LiDFP to high-stability interface: A targeted and persistent multistage strategy for lithium-rich cathode - Jin Zhu; Xiaosong Zhang; Denghui Ma; Lei Zhang; Yiyao Xiao; Keyu Zheng; Jiamin Duan; Shunjie Xu; Longhao Cao; Yinghui Li; Guanghua Guo; Xiuxia Zuo; et al. (Chemical Engineering Journal, 2026)

High-frequency redox fluctuations in deep-lacustrine basin and their impact on organic carbon burial: Records from micrometer-scale laminae in the Triassic Yanchang Formation Shale, Ordos Basin - Ke Li; Kelai Xi; Yingchang Cao; Zhe Zhao; Xiujuan Wang; Miruo Lin; Keyu Liu; Fang Hao (Science China Earth Sciences, 2026)

Transferable and adaptable full-field structural response reconstruction from sparse sensors via GraphSAGE–LSTM neural networks - Keyu Lai; Xiaoyou Wang; Yixian Li; Hong Guan; Yiming Zhang; Yong Xia (Engineering Structures, 2026)

Ankyrin-repeat transmembrane protein WAI-1 confers multiple disease resistance in wheat by activating autoimmunity - Qiuhong Wu; Wenling Li; Yongxing Chen; Huaizhi Zhang; Delin Li; Zhan Li; Fei Xiong; Guanghao Guo; Lei Dong; Xuejia Cui; Jingzhong Xie; Ping Lu; et al. (Science China Life Sciences, 2026)

Functional repositioning of aerobic granular sludge as a nitrite-producing pretreatment for mainstream Anammox driven by slowly biodegradable organic matter - Zongshuo Han; Xiaoying Zheng; Jiaqing Tao; Yunqing Li; Keyu Chen; Ruijie Hu; Yifan Zhou; Yang Zhang (Process Safety and Environmental Protection, 2026)

Combining medium coalescence filtration and combined fiber coalescence: A pilot study on treating washing wastewater from shipboard EGR systems - Yu Li; Jinwei Xue; Guangyao Zhang; Yiqian Liu; Haonan Liu; Keyu Wang; Xin Han; Qiang Yang (Journal of Environmental Chemical Engineering, 2026)

Thresholds and shifting drivers for the temporal dynamics of mycorrhizal symbiosis in a temperate grassland - Qiang Dong; Xin Guo; Keyu Chen; Shijie Ren; Yu Tang; Xinling Dai; Yaoming Li; Jing Zhang; Baoming Ji (Plant and Soil, 2026)

Seismic-attribute optimization for improving reservoir prediction integrating the spectral decomposition and automated machine learning - Keyu Ren; Wei Li; Lun Zhao; Wurong Wang; Jincai Wang; Han Wang; Yi Li; Linbo Qu; Dali Yue (Journal of Applied Geophysics, 2026)

Thermodynamically-driven selective phase reconstruction repairs kinetic of iron oxalate anodes for stable Li/Na storage - Yichong Kong; Binxin Yu; Keyu Zhang; Binbin Li; Bo Jin; Bin Yang; Yaochun Yao (Chemical Engineering Journal, 2026)

Opportunities to enhance sugarcane yield and gross margin under climate change through irrigation and planting date adaptation - Shijin Yao; De Li Liu; Bin Wang; Siyi Li; Jonathan K. Webb; Keyu Xiang; Alfredo Huete; Lihong Wu; Hao Quan; Qiang Yu (Irrigation Science, 2026)

Establishing tracer gas dilution as a potential reference method for in-stack CO2 emission metrology - Yayong Liu; Zhe Bi; Xiaoping Song; Chi Tu; Keyu Chen; Shao-Meng Li (Journal of Cleaner Production, 2026)

Alkali–organic synergy rewires microbial acid tolerance to restore nitrogen cycling in acidic soils - Mengke Li; Keyu Yao; Jean Damascene Harindintwali; Min Qian; Nan Wu; Yanwei Kan; Ziyi Song; Xian Xiao; Peng Liu; Yuan Zhao (Journal of Environmental Management, 2026)

RoofX-Net: A tailored approach to accurate multi-type rooftop segmentation in remote sensing images using edge and scale awareness - Keyu Chen; Tianlei Wang; Zhiyou Yang; Fan Li; Ma Luo; Ruoning Zhang; Hong Qu; Wenyu Chen (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Low‑intensity aeration enhances algal–bacterial synergy to improve nitrogen removal from wastewater with low carbon-to-nitrogen ratio - Yunqing Li; Xiaoying Zheng; Ruijie Hu; Jiaqing Tao; Zongshuo Han; Keyu Chen; Yifan Zhou; Yang Zhang; Wei Chen (Bioresource Technology, 2026)

‘1347B’ module confers durable stripe rust resistance in wheat - Hongkui Fu; Delin Li; Huaizhi Zhang; Yongxing Chen; Ping Lu; Miaomiao Li; Gaojie Wang; Keyu Zhu; Lei Dong; Jian Yang; Chunhuan Chen; Bin Bai; et al. (Theoretical and Applied Genetics, 2026)

Grazing-induced enhancement of rhizosphere effect on soil multifunctionality is linked to altered microbial life-history strategies in semiarid grasslands - Nuo Xu; Le Li; Yuhong Luo; Yunxiang Jin; Keyu Bai; Qiuli Bao; Jiahui Liu; Yufan Bao; Yuchun Yan (Agriculture, Ecosystems & Environment, 2026)

Defect-triggered S-scheme heterojunction coupled with single-molecular catalytic centers towards selective photocatalytic CO2 reduction to CO - Keyu Cui; Yujia Wang; Xingjing Zhang; Jiaming Li; Chunbo Liu; Liqiu Zhang; Hongjun Dong; Chunmei Li (Chemical Engineering Journal, 2026)

Projecting shifts in drought-induced thresholds for wheat yield loss under climate change in southeastern Australia - Keyu Xiang; Bin Wang; De Li Liu; Chao Chen; Fei Ji; Fangzheng Chen; Shijin Yao; Siyi Li; Alfredo Huete; Yi Li; Qiang Yu (Agricultural and Forest Meteorology, 2026)

Apoptotic extracellular vesicles: unveiling mechanisms, diverse functions, and biomedical implications - Xuan Li; Keyu Wang; Caining Wen; Haorui Li; Limei Xu; Yuanmin Zhang; Xiao Xu; Yujie Liang (Apoptosis, 2026)

Mapping biology in space: from spatial transcriptomics platforms to analytical tools and databases - Zi-Zhen Guo; Renyan Wu; Weixiang Li; Keyu Yang; Xuexiang Ying; Hamid Alinejad-Rokny; Youqiong Ye (Science Bulletin, 2026)

Biocontrol potential of Bacillus amyloliquefaciens LJ1 in enhancing disease resistance and quality preservation of Nanguo pears against Penicillium expansum - Zilong Li; Jiamin Jiang; Keyu Sun; Yan Ding; Shuhong Ye (Postharvest Biology and Technology, 2026)

Symbiotic food grade fermentation enhances the multifunctional photoprotective activity of Tricholoma matsutake through metabolic remodeling - Yongyan Pei; Zhiqing Tang; Keyu Lin; Hongliang Li; Yitong Chen; Hua Cao (Food Bioscience, 2026)

Future climate change increases the risk of wheat yield loss due to agricultural drought in southeastern Australia - Keyu Xiang; Bin Wang; De Li Liu; Chao Chen; Fei Ji; Shijin Yao; Siyi Li; Alfredo Huete; Yi Li; Qiang Yu (European Journal of Agronomy, 2026)

Effect of Ginkgo endophytic Rhodococcus sp. FY-5 on alleviating chilling injury of postharvest ‘Nanguo’ pear fruit - Jiamin Jiang; Zilong Li; Keyu Sun; Shuhong Ye (Postharvest Biology and Technology, 2026)

Bacillus amyloliquefaciens LJ1 from Nanguo Pear: Suppressing Penicillium expansum colonization and degrading patulin in postharvest disease management - Zilong Li; Jiamin Jiang; Keyu Sun; Shuhong Ye (Food Control, 2026)

Unraveling the drivers of corn yield response to optimization fertilization in plateau acidic red soils - Zhengfa Chen; Keyu Yan; Hui Yan; Xiaohan Mei; Chi Wang; Xingwei Chen; Wanli Hu; Bin Fu; Ming Ni; Zhiwu Li; Qingsong Duan; Yanmei Hu; et al. (Field Crops Research, 2026)

Soft-chemical topotactic pathway to (001)-faceted hollandite K-Fe-Ti oxides with accelerated Li+ migration - Xing Wang; Ling Che; Zihao Li; Zhigao Chen; Xingang Kong; Kun Zhang; Keyu Xie (Chemical Engineering Journal, 2026)

ACSL4 Inhibition by AS-252424 Protects Visual Function by Suppressing RGC Ferroptosis After Retinal Ischemia Reperfusion Injury - Keyu Liu; Zihao Lin; Wu Xiang; Jiayi Zhang; Xiaofeng Wu; Chenzhao Ma; Yantao Wei; Jiawei Wang; Jianqiao Li (Molecular Neurobiology, 2026)

Climate warming enhances sugarcane yield and increases annual harvest frequency in northern coastal New South Wales, Australia - Shijin Yao; De Li Liu; Bin Wang; Jonathan K. Webb; Siyi Li; Alfredo Huete; Keyu Xiang; Qiang Yu (Agricultural Systems, 2026)

Responses of Phytoplankton Bloom Magnitude Off the Yangtze River Estuary to the Zonal Position of the Northwest Pacific Subtropical High - Qiong Wu; Keyu Hu; Bo Li; Tianqi Xiong; Hui Chen; Shaofeng Wang (International Journal of Climatology, 2025)
The phytoplankton bloom magnitude (PBM) off the Yangtze River Estuary has important responses to the changes in the east–west position of the northwest Pacific subtropical high (NWPSH). The potential physical mechanism is analyzed through observations and a physical–biogeochemical model. Results reveal that the anomalously high precipitation in June–July increases the extension ranges of low salinity and high NO 3 concentration water in NWPSH westward extension years. However, due to persistent cloudy and rainy weather, the light condition is unfavorable for the explosive growth of phytoplankton. When the NWPSH moves northward in August, the study area is controlled by anomalously anticyclonic circulation; hot and sunny weather prevails, the nutrients carried by the Yangtze River discharge during the previous June–July period continue to extend toward Jeju Island with the diluted water, favoring the explosive growth of phytoplankton, and vice versa. Sensitivity experiments reveal that when the June–July averaged river discharge and nutrients in NWPSH westward extension years are twice those in normal years, the range of phytoplankton blooms in August can extend to 124.2° E. When the June–July averaged river discharge and nutrients in NWPSH westward extension years are only 0.5 times those in normal years, the range of phytoplankton blooms in August only extends to 123° E. Therefore, the changes in river discharge and nutrient expansion range caused by the east–west position changes of the NWPSH in June–July are important reference indicators for phytoplankton bloom variations throughout the summer. The study provides new scientific reference for seasonal phytoplankton bloom forecasting off the Yangtze River Estuary.

Deciphering gut microbial dynamics and multi-omics changes in yogurt-based dietary interventions - Qiuwen He; Yaru Sun; Hao Jin; Lai-Yu Kwok; Teng Ma; Keyu Quan; Yalin Li; Xuan Shi; Zhihong Sun; Heping Zhang (Science Bulletin, 2025)

Marine flooding induced basinal brine mixing and carbonate cementation: An example from Cretaceous ultra-deep clastic reservoirs in the Kuqa Depression, western China - Shunyu Wang; Jian Wang; Keyu Liu; Yong Li; Zhenkun Li; Meiyi Chen; Leilei Yang (Marine and Petroleum Geology, 2025)

Cumulative droughts and legacy effects decreased long-term growth resilience in Pinus massoniana in the middle Dabie Mountains - Yameng Liu; Jinkuan Li; Jianfeng Peng; Jiaxin Li; Xiaoxu Wei; Keyu Zhang (Dendrochronologia, 2025)

Harnessing dental stem cell-extracellular vesicles for osteogenesis, immunomodulation, angiogenesis, and neurogenesis during bone regeneration - Xi Xiang; Jianwen Li; Danyuan Xie; Keyu Lv; Hanyang Yu; Xinwei Han; Ying Ruan; Tingting Sun; Xuguang Gao; Youguang Lu; Janak L. Pathak; Sujuan Zeng (Chemical Engineering Journal, 2025)

Thiol-functionalized dual network polysaccharide microgels for synergistic Patulin adsorption and gut-liver axis protection via delivery and controlled release of Ginkgo Biloba extract - Keyu Sun; Ziwuzhen Wang; Jiamin Jiang; Zilong Li; Shuhong Ye (Chemical Engineering Journal, 2025)

Delayed progression of diabetic cataractogenesis and retinopathy by topical administration of highly biocompatible carbon dots derived from Scutellaria barbata and Herba hedyotis diffusae - Jiawei Wang; Yihan Zhao; Xueying Yang; Can Li; Keyu Liu; Chenzhao Ma; Yanyan Jiang; Jianqiao Li (Chemical Engineering Journal, 2025)

Architectural design of multidimensional carbonaceous structures: Synergistic pathways enabling high-energy silicon-based anodes - Wendi Chen; Lingjun Guo; Ruonan Zhang; Guangyao Liu; Yue Ma; Dian Jia; Hejun Li; Keyu Xie (Chemical Engineering Journal, 2025)

Design of amides and long-chain alkyl alcohols for high selectivity recovery of titanium and iron from ilmenite - Keyu Zhu; Qinqin Yu; Guokang Hu; Changchang Chen; Yanni Li; Jiacan Tang; Weiwei Zhang (Minerals Engineering, 2025)

Metagenomic analysis of bacterial fitness and plasmids carrying blaTEM-1 and virulence genes before and after cleaning and disinfection in pig slaughterhouses - Shanshan Chu; Yan Chen; Zhuoqun Xu; Jie Zhou; Keyu Li; Qi Zhang; Min Qian; Jianzhong Han; Daofeng Qu (Journal of Hazardous Materials, 2025)

Bouquet-like β-alanine modified Bi4O5Br2/Fe-CeO2 Z-scheme heterojunction photocatalyst for degradation of ciprofloxacin: potential application, toxicity evaluation and degradation mechanism - Yu Chen; Pengfei Zhu; Xuemei Chen; Xinglin Li; Keyu Pu; Jiayi Fan (Environmental Research, 2025)

Straw humification coefficient and its relation to soil carbon and nitrogen status - Yue Sun; Huiying Wang; Wei Jia; Keyu Ren; Bingjie Li; Hongqin Zou; Yinghua Duan; Minggang Xu (Journal of Environmental Management, 2025)

Sediment remediation by La-MOF/PP fabric coupled with phosphate solubilizing bacteria: Phosphate activation and removal - Qinqin He; Wenhao Lu; Hang Zhou; Xiaonan Ji; Wei Hu; Kuo Pang; Zedong Teng; Xin Zhao; Lintao Wang; Keyu Fan; Feichao Hu; Min Li (Journal of Environmental Chemical Engineering, 2025)

Mechanisms of Priestia megaterium PH3 in alleviating postharvest disease caused by Penicillium expansum in Nanguo pear fruit - Zilong Li; Jiamin Jiang; Keyu Sun; Shuhong Ye (Food Microbiology, 2025)

Ecosystem engineering and global changes are increasingly enhancing China’s terrestrial carbon sinks - Mengyu Zhang; Honglin He; Li Zhang; Xiaoli Ren; Liang Shi; Guirui Yu; Zhong’en Niu; Keyu Qin; Tiecheng Li (Resources, Conservation and Recycling, 2025)

Regional NDVI reconstruction based on tree-ring width of Pinus massoniana Lamb. in the north-south transition zone of China - Kunyu Peng; Yameng Liu; Keyu Zhang; Jiaxin Li; Jinkuan Li; Xiaoxu Wei; Mengyu Wang; Jianfeng Peng (Dendrochronologia, 2025)

Climate change and social turmoil in the late Qing Dynasty revealed by tree rings - Jinkuan Li; Jiaxin Li; Yameng Liu; Keyu Zhang; Xiaoxu Wei; Mengyu Wang; Jianfeng Peng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Temporal-spatial analysis and geological interpretation of groundwater dynamics in a marine aquifer - Keyu Gong; Zhang Wen; Qinghua Li; Qi Zhu (Journal of Hydrology, 2025)

The potentials of uncertainty analysis and Bayesian optimization in HONO source modeling diagnosis and improvement - Jinlong Zhang; Wending Wang; Keyu Zhu; Zhijiong Huang; Li Sheng; Songdi Liao; Xin Yuan; Yanan Hu; Jiangping Liu; Mengxue Tang; Xiaofeng Huang; Jie Li; et al. (Environmental Research, 2025)

Activation of the Nrf2 Signaling Pathway by Tetrahydroberberine Suppresses Ferroptosis and Enhances Functional Recovery Following Spinal Cord Injury - Xiang Li; Heng Yu; Rongjie Liu; Jiansen Miao; Junlei Lv; Shu Yang; Yuxuan Zhu; Yan Chen; Keyu Lu; Chongan Huang; Xiangyang Wang (Molecular Neurobiology, 2025)

Impact of Proton Pump Inhibitors on Osimertinib-Induced Cardiotoxicity in NSCLC Patients - Haitao Wang; Sinan Ma; Weijia Huang; Keyu Chen; Jiao Xie; Na Wang; Youjia Li; Qianting Yang; Xin Yang; Yan Wang (Cardiovascular Toxicology, 2025)

Investigating the potential of magnesium isotopes in bioarchaeology: evidence from the Zaoshugounao Site - Keyu Liu; Xue Ling; Haifeng Dou; Yaopeng Qian; Zhen Wang; Yue Li; Kangjun Huang; Chunlei Zong (Archaeological and Anthropological Sciences, 2025)

A genomic compendium of cultivated food-derived lactic acid bacteria unveils their contributions to human health - Hao Jin; Keyu Quan; Lijun You; Lai-Yu Kwok; Teng Ma; Yalin Li; Xuan Shi; Xin Su; Ruirui Lv; Zhihong Sun; Wenjun Liu; Heping Zhang (Science Bulletin, 2025)

An enhanced nitrate-to-ammonia conversion through bimetallic synergism and architectural effects - Yuyue Zhu; Keyu Zhou; Donglin Zhao; Huiying Li; Guangyin Fan; Pengyao You (Journal of Environmental Chemical Engineering, 2025)

Sensitive lateral flow immunoassay enabled by signal amplification strategy with high active oxidase-like nanozymes - Jie Zhu; Yunhui Cheng; Xufeng Wang; Hao Wu; Ye Jiao; Keyu Xing; Li Yao; Pei Jia; Zhou Xu (Food Bioscience, 2025)

How does greenness contribute to reducing lung cancer risks associated with particulate matter exposure? - Keyu Luo; Huagui Guo; Weifeng Li; Jiansheng Wu (Atmospheric Pollution Research, 2025)

Response of sea-surface partial pressure of CO2 to ENSO events over the Taiwan Strait - Keyu Hu; Qiong Wu; Tianqi Xiong; Bo Li; Peng Bai; Zhenxin Ruan; Chengcheng Yu (Acta Oceanologica Sinica, 2025)

Differential crop yield responses to elevated CO2 attributed to varying biomass part stimulations: a meta-analysis - Yanling Bai; Liu Liu; Hao Li; Xi Peng; Keyu Fa; Guanhua Huang (Plant and Soil, 2025)

Genotyping and antimicrobial susceptibility of Aeromonas veronii isolated from aquatic animals in Sichuan, China - Kun Peng; Silu Tian; Longjun Deng; Yu Yuan; Zixuan Cheng; Tiancai Li; Keyu Zhou; Jingyi Lin; Yi Geng (Antonie van Leeuwenhoek, 2025)

Formation and control of heterocyclic amines and advanced glycation end products in traditional Chinese braised pork belly: The role of food additives - Keyu Lu; Qiaochun Chen; Jiayi He; Qian Zhou; Siqian Li; Mingfu Wang (Food Research International, 2025)

The impacts of China’s sustainable financing policy on environmental, social and corporate governance (ESG) performance - Haoyu Li; Xing Gao; Xingman Zhang; Keyu Zhai; Yantao Ling; Mengqiu Cao (Environment, Development and Sustainability, 2025)

How bedding-parallel fractures affect fluid activity in a relatively closed lacustrine shales system: Evidence from calcite veins - Zilong Li; Kelai Xi; Xiaobing Niu; Xiujuan Wang; Wenzhong Ma; Xiao Hui; Jiangyan Liu; Changyu Fan; Miruo Lin; Keyu Liu; Yingchang Cao (Marine and Petroleum Geology, 2025)

Construction and characterization of probiotic intestinal-targeted delivery system based on complex coacervation and double-emulsion structure - Nuocheng Xu; Yutong Feng; Huiping Wan; Zilong Li; Keyu Sun; Shuhong Ye (Food Hydrocolloids, 2025)

Soil with high plant available water capacity can mitigate the risk of wheat growth under drought conditions in southeastern Australia - Keyu Xiang; Bin Wang; De Li Liu; Chao Chen; Fei Ji; Yanmin Yang; Siyi Li; Mingxia Huang; Alfredo Huete; Qiang Yu (European Journal of Agronomy, 2025)

Cost effective selective separation of indium and germanium from zinc processing waste leach liquor using D2EHPA-YW100 synergistic system and selective stripping with HCl and NH4F - Chen Wang; Junxian Hu; Keyu Zhang; Shaoze Zhang; Yin Li; Yaochun Yao (Hydrometallurgy, 2025)

Stability of China's terrestrial ecosystems carbon sink during 2000-2020 - Liang Shi; Honglin He; Li Zhang; Junbang Wang; Xiaoli Ren; Guirui Yu; Peng Hou; Jixi Gao; Bin Chen; Keyu Qin; Lili Feng; Shaoqiang Wang; et al. (Resources, Conservation and Recycling, 2025)

Spatiotemporal changes and management measure to enhance ecosystem services in the Mongolian Plateau - Xianhua Wei; Xiaodong Wu; Dong Wang; Tonghua Wu; Ren Li; Guojie Hu; Defu Zou; Keyu Bai; Yadong Liu; Xuchun Yan; Xiaoying Fan; Avirmed Dashtseren; et al. (Environmental Development, 2024)

Crystal and micro-nano structure bidirectional regulation of iron oxalate for high-lithium storage and ultralong-cycling life via ultrasound assistance - Qing Zhao; Keyu Zhang; Geng Gao; Bo Jin; Guangping Zi; Rui Yan; Binbin Li; Bin Yang; Yaochun Yao (Chemical Engineering Journal, 2024)

Spatial mapping of greenhouse gases using a UAV monitoring platform over a megacity in China - Tianran Han; Conghui Xie; Yanrong Yang; Yuheng Zhang; Yufei Huang; Yayong Liu; Keyu Chen; Haijiong Sun; Jietao Zhou; Chang Liu; Junfei Guo; Zhijun Wu; et al. (Science of The Total Environment, 2024)

Optimizing pollen germination and subcellular dynamics in pollen tube of Torreya grandis - Shuai Hu; Chengqiao Wang; Rui Zhang; Yanli Gao; Keyu Li; Jinbo Shen (Plant Science, 2024)

One-stone-for-two-birds strategy to achieve effective electrochemical nitrate reduction towards ammonia synthesis with Ru doped cobalt tungstate - Xue Bai; Keyu Zhou; Lan Lin; Huiying Li; Qianggen Li; Guangyin Fan (Fuel, 2024)

3D reconfigurable hydroxylated carbon nanotubes-based water evaporators with long-distance transportation for continuous vapor generation - Youqiang Huang; Pengjie Zhong; Ningning Zhu; Yinyan Li; Zhen Xiao; Keyu Han; Beibei Xu; Shiqing Xu; Gongxun Bai (Chemical Engineering Journal, 2024)

LNP-mRNA delivers TNF-α antibody to deep cartilage and protects against osteoarthritis - Baixing Li; Lei Cui; Keyu Kong; Yichuan Pang; Yan Chen; Shuning Zhang; Fangfang Wang; Tangjun Zhou; Yunfeng Hua; Mi Cao; Hongtao Xu; An Qin; et al. (Chemical Engineering Journal, 2024)

Petaloid CoP/FeP Composites: Efficiently bifunctional cathode electrochemical oxygen catalysts for aqueous and Solid-State Zinc-Air batteries - Keyu Chen; Lu Wang; Jilan Long; Fei Zhao; Li Kang (Chemical Engineering Journal, 2024)

Development of a novel Al-Si microcapsules with heat-resistant, high latent heat, and efficient solar heat absorption - Runda Qian; Keyu Weng; Meng Liu; Li Huang; Deqiu Zou (Chemical Engineering Journal, 2024)

Increased ecological land and atmospheric CO2 dominate the growth of ecosystem carbon sinks under the regulation of environmental conditions in national key ecological function zones in China - Mengyu Zhang; Honglin He; Li Zhang; Guirui Yu; Xiaoli Ren; Yan Lv; Zhong'en Niu; Keyu Qin; Yanni Gao (Journal of Environmental Management, 2024)

Unleashing hidden carbon sequestration potential: A case study of the Greater Bay Area, China - Keyu Luo; Zhenyu Wang; Weifeng Li; Jiansheng Wu (Urban Climate, 2024)

Effects of seasoning addition and cooking conditions on the formation of free and protein-bound heterocyclic amines and advanced glycation end products in braised lamb - Qiaochun Chen; Keyu Lu; Jiayi He; Qian Zhou; Siqian Li; Hui Xu; Yuting Su; Mingfu Wang (Food Chemistry, 2024)

May–June relative humidity variation recorded by tree ring widths of Pinus armandii Franch since 1863 in the Funiu Mountains, central China - Jinkuan Li; Kunyu Peng; Xiaoxu Wei; Yameng Liu; Jiaxin Li; Meng Peng; Xuan Li; Keyu Zhang; Jianfeng Peng (Quaternary International, 2024)

Boosting activity on CoFe layered double hydroxide by doping and heterostructure as a bifunctional electrocatalyst for efficient overall water splitting - Jian Tang; Junxian Hu; Xuanli Chen; Bin Yang; Keyu Zhang; Yin Li; Yaochun Yao; Shaoze Zhang (Fuel, 2024)

A novel magnetic resonance tuning-magnetic relaxation switching sensor based on Gd-MOF/USPIO assembly for sensitive and convenient aflatoxin B1 detection - Shiqin Dai; Keyu Xing; Yanna Jiao; Shaoyi Yu; Xingyu Yang; Li Yao; Pei Jia; Yunhui Cheng; Zhou Xu (Food Chemistry, 2024)

Optimal design of transverse dampers incorporating inherent stiffness effects for stay cable vibration control: A case study with wire rope dampers - Keyu Lai; Wei Fan; Zhengqing Chen; Huawei Niu; Lingfei Ma; Shouying Li (Engineering Structures, 2024)

Investigation on Phenomics of Traditional Chinese Medicine from the Diabetes - Boxun Zhang; Lijuan Zhou; Keyu Chen; Xinyi Fang; Qingwei Li; Zezheng Gao; Fengmei Lian; Min Li; Jiaxing Tian; Linhua Zhao; Xiaolin Tong (Phenomics, 2024)
With thousands of years of application history, traditional Chinese medicine (TCM) has unique advantages in the prevention of various chronic diseases, and in recent years, the development of TCM has presented a situation where opportunities and challenges coexist. Phenomics is an emerging area of life science research, which has numerous similarities to the cognitive perspective of TCM. Thus, how to carry out the interdisciplinary research between TCM and phenomics deserves in-depth discussion. Diabetes is one of the most common chronic non-communicable diseases around the world, and TCM plays an important role in all stages of diabetes treatment, but the molecular mechanisms are difficult to elucidate. Phenomics research can not only reveal the hidden scientific connotations of TCM, but also provide a bridge for the confluence and complementary between TCM and Western medicine. Facing the challenges of the TCM phenomics research, we suggest applying the State-target theory (STT) to overall plan relevant researches, namely, focusing on the disease development, change trends, and core targets of each stage, and to deepen the understanding of TCM disease phenotypes and the therapeutic mechanisms of herbal medicine.

Frond characteristics of Cyrillopteris (ex. Odontopteris) orbicularis (Halle) comb. et emend. nov.: New evidence from the Permian Upper Shihezi (Upper Shihhotse) Formation of North China - Mingli Wan; Dandan Li; Shan Wan; Wan Yang; Weiming Zhou; Keyu Wang; Kaige Jiang; Jun Wang (Review of Palaeobotany and Palynology, 2024)

Four-decades of sediment transport variations in the Yellow River on the Loess Plateau using Landsat imagery - Zhiqiang Qiu; Dong Liu; Mengwei Duan; Panpan Chen; Chen Yang; Keyu Li; Hongtao Duan (Remote Sensing of Environment, 2024)

Occurrence of ochratoxin A in Sichuan bacon from different geographical regions and characterization and biocontrol of ochratoxigenic Aspergillus westerdijkiae strain 21G2-1A - Kaidi Hu; Keyu Guo; Xingjie Wang; Song Wang; Jianlong Li; Qin Li; Ning Zhao; Aiping Liu; Li He; Xinjie Hu; Yong Yang; Likou Zou; et al. (Food Research International, 2024)

Porous rod-like structured ternary nitride heterocatalyst Co3Mo3N/Ni3Mo3N for efficient and stable hydrogen evolution reaction - Jian Tang; Shaoze Zhang; Yixing Zeng; Bin Yang; Keyu Zhang; Yin Li; Yaochun Yao; Junxian Hu (Chemical Engineering Journal, 2024)

Effect of hydrothermal carbonization on pyrolysis behavior, nutrients and metal species distribution in municipal sludge - Changhao Liu; Zhengbo Yue; Ding Ma; Keyu Li; Zhilin Xie; Tianqin Zhang; Jin Wang (Bioresource Technology, 2024)

Effects of natural extract from medicinal herbs on broilers experimentally infected with Eimeria tenella - Yuanyuan Jiang; Yujuan Zeng; Keyu Chen; Haoran Cheng; Songjiang Dai; Xuexue Deng; Long Wang; Jinqiu Liao; Ruiwu Yang; Li Zhang (Veterinary Parasitology, 2024)

Integration of hydrothermal liquefied sludge as wastewater for anaerobic treatment and energy recovery: Aqueous phase characterization, anaerobic digestion performance and energy balance analysis - Changhao Liu; Zhengbo Yue; Ding Ma; Keyu Li; Pengcheng Zhao; Manyi Yang; Jin Wang (Journal of Water Process Engineering, 2024)

Application of nisin-embedded pectin microcapsules for ‘Guiqi’ mango fruit postharvest preservation - Wenqing Liu; Keyu Huang; Zhimei Tan; Chenshu Wang; Tongquan Wen; Liyuan Huang; Fangxue Hang; Caifeng Xie; Shupei Wang; Kai Li (Food Packaging and Shelf Life, 2024)

The fundamentals, progress, and perspectives of transition-metal dichalcogenides (TMDs) applied in advanced oxidation processes - Hao Huang; Mengyang Zhang; Keyu Xu; Yanling Zhuang; Yue Li; Longlu Wang (Chemical Engineering Journal, 2024)

ERS Mediated by GRP-78/PERK/CHOP Signaling Is Involved in Fluoride-Induced Ameloblast Apoptosis - Li Jinyi; Yang Keyu; Dai Shanshan; He Shuyang; Liu Ruirui; Guo Qingyu; Liu Fei (Biological Trace Element Research, 2024)

Bufogarlides A-C, three new bufadienolides with Δ 14,15 double bond from the skins of Bufo bufo gargarizans - Lingjie Meng; Qinghong Kong; Jianxun Xie; Feng Pan; Keyu Lu; Sanhua Li; Yiling Li; Di Zhang; Yun Liu (Natural Product Research, 2024)

Ibuprofen inhibits anaplastic thyroid cells in vivo and in vitro by triggering NLRP3-ASC-GSDMD-dependent pyroptosis - Haohao Guo; Runsheng Ma; Yifei Zhang; Keyu Yin; Gongbo Du; Fanxiang Yin; Hongqiang Li; Ziyang Wang; Detao Yin (Inflammopharmacology, 2024)
Pyroptosis is a novel type of proinflammatory programmed cell death that is associated with inflammation, immunity, and cancer. Anaplastic thyroid carcinoma (ATC) has a high fatality rate, and there is no effective or standard treatment. The disease progresses rapidly and these tumors can invade the trachea and esophagus, leading to breathing and swallowing difficulties. Hence, new treatment methods are greatly needed. Ibuprofen is a common drug that can exert antitumor effects in some cancers. In this study, we demonstrated in vitro and in vivo that ibuprofen can induce ATC pyroptosis. Hence, we treated C643 and OCUT-2C ATC cells with ibuprofen and found that several dying cells presented the characteristic morphological features of pyroptosis, such as bubble-like swelling and membrane rupture, accompanied by activation of ASC and NLRP3 and cleavage of GSDMD. Along with the increased release of LDH, ibuprofen treatment promoted apoptosis and inhibited viability, invasion, and migration. However, overexpression of GSDMD significantly inhibited ibuprofen-induced pyroptosis. In vivo, research has demonstrated that thyroid tumor growth in nude mice can be suppressed by ibuprofen-induced pyroptosis in a dose-dependent manner. In this research, we explored a new mechanism by which ibuprofen inhibits ATC growth and progression and highlighted its promise as a therapeutic agent for ATC.

Long-term grazing exacerbates soil microbial carbon and phosphorus limitations in the desert steppe of Inner Mongolia - A study based on enzyme kinetics - Shaoyu Li; Bin Zhang; Yanan Li; Tianqi Zhao; Jiahua Zheng; Jirong Qiao; Feng Zhang; Carlo Fadda; Devra Jarvis; Nadia Bergamini; Keyu Bai; Zongwen Zhang; et al. (Applied Soil Ecology, 2024)

Long-term fencing can't benefit plant and microbial network stability of alpine meadow and alpine steppe in Three-River-Source National Park - Keyu Chen; Sen Xing; Hailan Shi; Yu Tang; Mingxin Yang; Qiang Gu; Yaoming Li; Jing Zhang; Baoming Ji (Science of The Total Environment, 2023)

Enhancing the sewage treatment effect, reducing membrane fouling, and increasing microbial community diversity by a novel biofiller-carrying functional bacteria Rhodococcus sp. CPZ24 in a moving bed biofilm reactor - Peizhen Chen; Dongkai Chen; Bo Yang; Keyu Zhang; Shaopeng Li (Journal of Water Process Engineering, 2023)

The iLABdb: a web-based integrated lactic acid bacteria database - Hao Jin; Teng Ma; Lin Chen; Lai-Yu Kwok; Keyu Quan; Yalin Li; Zeng Zhang; Tong Chen; Jiachao Zhang; Zhihong Sun; Heping Zhang (Science Bulletin, 2023)

Revealing continuous hydrocarbon generation and shale oil accumulation of saline lacustrine source rocks by sequential extraction - Wenwen Li; Jian Cao; Wenxuan Hu; Yong Tang; Baoli Xiang; Wanyun Ma; Wenjun He; Keyu Tao; Yingqi Wang (Fuel, 2023)

Extraction kinetics of separating molybdenum(Ⅵ) over iron(Ⅲ) from high acid leach solutions with mixtures of P507 and N235 - Miaomiao Peng; Keyu Shen; Yangjing Tan; Zhiyi Hu; Chun Liu; Zhixiong Liu; Wenbin Yan; Jun Hua; Fei Li (Minerals Engineering, 2023)

Thermal pyrolysis-induced shale micro-cracks: 3D characterization and implication for reservoir stimulation - Chao Qi; Jie Liu; Keyu Liu; Jincai Tuo; Lina Sun; Wanying Huang; Shijie Li; Klaus Regenauer-Lieb (Gas Science and Engineering, 2023)

Proteomic profiling of purified avian leukosis virus subgroup J particles - Sheng Chen; Yiming Yan; Liguo Gao; Shuang Gao; Keyu Feng; Hongxin Li; Xinheng Zhang; Weiguo Chen; Feng Chen; Qingmei Xie (Veterinary Microbiology, 2023)

Targeting gut microbiota and metabolism as the major probiotic mechanism - An evidence-based review - Teng Ma; Xin Shen; Xuan Shi; Hafiz Arbab Sakandar; Keyu Quan; Yalin Li; Hao Jin; Lai-Yu Kwok; Heping Zhang; Zhihong Sun (Trends in Food Science & Technology, 2023)

Geochemistry of syntaxial calcite veins in ultra-deep sandstone reservoirs from the Kuqa depression, western China - Shunyu Wang; Keyu Liu; Jian Wang; Yong Li; Zhenkun Li; Haijun Yang; Tao Mo (Journal of Structural Geology, 2023)

Target-triggered Fe3O4@NPC-UCNPs assembly for photoactivatable biosensing of Aflatoxin B1 - Zhou Xu; Shaoyi Yu; Xinyi Xie; Qingxia Li; Li Ding; Maolong Chen; Jia Tu; Keyu Xing; Yunhui Cheng (Chemical Engineering Journal, 2023)

Achieving high yield and nitrogen agronomic efficiency by coupling wheat varieties with soil fertility - Keyu Ren; Minggang Xu; Rong Li; Lei Zheng; Huiying Wang; Shaogui Liu; Wenju Zhang; Yinghua Duan; Changai Lu (Science of The Total Environment, 2023)

Effect of using construction and demolition waste as substrate on methane and carbon dioxide emissions from green roofs - Xinping Li; Yuanmao Lin; Xiaoling Liu; Jie Liang; Xin Yang; Ke Zhang; Bing Jiang; Hongbing Luo; Lin Li; Zhaolan Wei; Xiaochan An; Wei Chen; et al. (Ecological Engineering, 2023)

The influence of CO2 partial pressure on the stability of dawsonite-based on water-rock physical experiment and numerical simulation - Fulai Li; Chun Zhang; Kaining Wang; Wenkuan Ma; Jianlei Yang; Qizhen Du; Shaogui Deng; Keyu Liu (Applied Geochemistry, 2023)

Geostatistical simulations of the spatial variability of hydraulic conductivity in an alluvial-marine sedimentary system in Beihai City, China - Keyu Gong; Zhang Wen; Qinghua Li; Qi Zhu (Journal of Hydrology, 2023)

Spatiotemporal variations and driving factors for potential wind erosion on the Mongolian Plateau - Xianhua Wei; Xiaodong Wu; Dong Wang; Tonghua Wu; Ren Li; Guojie Hu; Defu Zou; Keyu Bai; Xin Ma; Yadong Liu; Xuchun Yan; Xiaoying Fan; et al. (Science of The Total Environment, 2023)

Performance of wire rope damper in vibration reduction of stay cable - Keyu Lai; Wei Fan; Zhengqing Chen; Chao Yang; Zhiwen Liu; Shouying Li (Engineering Structures, 2023)

Simultaneous adsorption and fluorescent detection of Cr(VI) via lanthanide coordinating polymeric porous microparticles - Qimeng Ran; Zilin Fan; Xinkai Guo; Xiulan Li; Keyu Yi; Xiaobo Liu; Kun Jia (Chemical Engineering Journal, 2023)

A petroliferous Ediacaran microbial-dominated carbonate reservoir play in the central Sichuan Basin, China: Characteristics and diagenetic evolution - Changwei Li; Keyu Liu; Jianliang Liu (Precambrian Research, 2023)

Carbazole and polyhalogenated carbazoles in the marine environment around the Zhoushan Archipelago: Distribution characteristics, environmental behavior, and sources - Zhaochao Deng; Songtao Hu; Leiming Tang; Lingbo Jiang; Junyu He; Keyu Shen; Yongjiu Xu; Rijin Jiang; Tiejun Li; Chunlei Chen; Bairu Chen; Hanghai Zhou; et al. (Journal of Hazardous Materials, 2023)

Characteristics of sea ice kinematics from the marginal ice zone to the packed ice zone observed by buoys deployed during the 9th Chinese Arctic Expedition - Xiaomin Chang; Longchun Ye; Guangyu Zuo; Jingyue Li; Keyu Wei; Yinke Dou (Acta Oceanologica Sinica, 2022)

A comprehensive review of the circulation of microplastics in aquatic ecosystem using scientometric method - Yuan Gao; Keyu Fan; Zini Lai; Chao Wang; Haiyan Li; Qianfu Liu (Environmental Science and Pollution Research, 2022)

Fine mapping of powdery mildew resistance gene MlWE74 derived from wild emmer wheat (Triticum turgidum ssp. dicoccoides) in an NBS-LRR gene cluster - Keyu Zhu; Miaomiao Li; Haibin Wu; Deyun Zhang; Lingli Dong; Qiuhong Wu; Yongxing Chen; Jingzhong Xie; Ping Lu; Guanghao Guo; Huaizhi Zhang; Panpan Zhang; et al. (Theoretical and Applied Genetics, 2022)

Occurrence and distribution characteristics of antibiotic resistance genes in sediments between urban and rural of the Liaohe River Basin, China - Guangshui Na; Keyu Zhang; Hui Gao; Ruijing Li; Shuaichen Jin; Fuqiang Zhao; Haibo Zhang; Shisheng Li (Environmental Science and Pollution Research, 2021)

Revisiting Rhenium-Osmium Isotopic Investigations of Petroleum Systems: From Geochemical Behaviours to Geological Interpretations - Shao-Jie Li; Xuan-Ce Wang; Simon A. Wilde; Zhuyin Chu; Chaofeng Li; Sheng He; Keyu Liu; Xingzhi Ma; Yuxiang Zhang (Journal of Earth Science, 2021)

Optimized production and characterization of cation-independent bioflocculant produced by Klebsiella sp. 59L - Keyu Fang; Boji Wang; Yao Zhang; Hongjing Li (Environmental Science and Pollution Research, 2021)

Identification and fine mapping of spot blotch (Bipolaris sorokiniana) resistance gene Sb4 in wheat - Panpan Zhang; Guanghao Guo; Qiuhong Wu; Yongxing Chen; Jingzhong Xie; Ping Lu; Beibei Li; Lingli Dong; Miaomiao Li; Rongge Wang; Chengguo Yuan; Huaizhi Zhang; et al. (Theoretical and Applied Genetics, 2020)

The total suitability of water yield and carbon sequestration under multi-scenario simulations in the Weihe watershed, China - Li Zeng; Jing Li; Keyu Qin; Jingya Liu; Zixiang Zhou; Yumeng Zhang (Environmental Science and Pollution Research, 2020)

Roles of sulfur compounds in growth and alkaline phosphatase activities of Microcystis aeruginosa under phosphorus deficiency stress - En Xie; Fangfang Li; Chaozi Wang; Wei Shi; Chen Huang; Keyu Fa; Xiao Zhao; Dayi Zhang (Environmental Science and Pollution Research, 2020)

Identified trans-splicing of YELLOW-FRUITED TOMATO 2 encoding the PHYTOENE SYNTHASE 1 protein alters fruit color by map-based cloning, functional complementation and RACE - Lulu Chen; Wenzhen Li; Yongpeng Li; Xuechao Feng; Keyu Du; Ge Wang; Lingxia Zhao (Plant Molecular Biology, 2019)

Correction to: Cellular distribution of cadmium in two amaranth (Amaranthus mangostanus L.) cultivars differing in cadmium accumulation - Keyu Chi; Rong Zou; Li Wang; Wenmin Huo; Hongli Fan (Environmental Science and Pollution Research, 2019)

Cellular distribution of cadmium in two amaranth (Amaranthus mangostanus L.) cultivars differing in cadmium accumulation - Keyu Chi; Rong Zou; Li Wang; Wenmin Huo; Hongli Fan (Environmental Science and Pollution Research, 2019)

Construction of a small-caliber tissue-engineered blood vessel using icariin-loaded β-cyclodextrin sulfate for in situ anticoagulation and endothelialization - Jingyuan Yang; Keyu Wei; Yeqin Wang; Yanzhao Li; Ning Ding; Da Huo; Tianran Wang; Guanyuan Yang; Mingcan Yang; Tan Ju; Weng Zeng; Chuhong Zhu (Science China Life Sciences, 2018)

Taking climate, land use, and social economy into estimation of carbon budget in the Guanzhong-Tianshui Economic Region of China - Ting Li; Jing Li; Zixiang Zhou; Yanze Wang; Xiaonan Yang; Keyu Qin; Jingya Liu (Environmental Science and Pollution Research, 2017)

Genetic manipulation of a transcription-regulating sequence of porcine reproductive and respiratory syndrome virus reveals key nucleotides determining its activity - Haihong Zheng; Keyu Zhang; Xing-Quan Zhu; Changlong Liu; Jiaqi Lu; Fei Gao; Yan Zhou; Hao Zheng; Tao Lin; Liwei Li; Guangzhi Tong; Zuzhang Wei; et al. (Archives of Virology, 2014)

Impact of Rock Heterogeneity on Interactions of Microbial-Enhanced Oil Recovery Processes - Jian Li; Jishan Liu; Michael G. Trefry; Keyu Liu; Jungho Park; Bashirul Haq; Colin D. Johnston; Michael B. Clennell; Herbert Volk (Transport in Porous Media, 2012)

Molecular characterization, recombinant expression in Escherichia coli and biological activity of (S)-Tetrahydroberberine oxidase from Corydalis saxicola Bunt - Keyu Chen; Ji Ye; Chang Liu; Peng Di; JunFeng Chen; Ying Xiao; HuiLiang Li; WeiDong Zhang (Molecular Biology Reports, 2012)

Replicative senescence of human bone marrow and umbilical cord derived mesenchymal stem cells and their differentiation to adipocytes and osteoblasts - HuanChen Cheng; Lin Qiu; Jun Ma; Hao Zhang; Mei Cheng; Wei Li; Xuefei Zhao; Keyu Liu (Molecular Biology Reports, 2011)

Interactions of Microbial-Enhanced Oil Recovery Processes - Jian Li; Jishan Liu; Michael G. Trefry; Jungho Park; Keyu Liu; Bashirul Haq; Colin D. Johnston; Herbert Volk (Transport in Porous Media, 2011)

High-resolution genetic mapping of bacterial blight resistance gene Xa10 - Keyu Gu; Jatinder Singh Sangha; Yin Li; Zhongchao Yin (Theoretical and Applied Genetics, 2008)